2007
DOI: 10.1074/jbc.m702876200
|View full text |Cite
|
Sign up to set email alerts
|

Annexin 1 Cleavage in Activated Neutrophils

Abstract: Annexin 1 is an anti-inflammatory protein that plays a key role in innate immunity by modulating the activation of several types of cells, including neutrophils. Here we have developed a cleavage assay using tagged annexin 1 and observed marked activity in the membrane fraction of activated neutrophils. A combination of inhibitors, transfected cells, and proteomic analyses allowed us to identify proteinase 3 as the main enzyme responsible for this cleavage in the N terminus region of the protein, at least in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 36 publications
5
129
0
4
Order By: Relevance
“…The AnxA1 N-terminal region is the site of attack by many proteases that may either lead to the inactivation of the protein (15) or release of peptides endowed with distinct bioactions to the parent protein (32). Thus, we assessed cleavage of AnxA1 2-50 by human PR3 and HNE, two enzymes associated with pathogenesis in vascular (33) and lung (34) diseases, but also abundant in inflammatory exudates (15,16). At variance from AnxA1, which in similar experimental settings is cleaved at positions 11, 22, and 36 (35), the shorter 50-aa-long sequence revealed a novel cleavage site at position 25.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AnxA1 N-terminal region is the site of attack by many proteases that may either lead to the inactivation of the protein (15) or release of peptides endowed with distinct bioactions to the parent protein (32). Thus, we assessed cleavage of AnxA1 2-50 by human PR3 and HNE, two enzymes associated with pathogenesis in vascular (33) and lung (34) diseases, but also abundant in inflammatory exudates (15,16). At variance from AnxA1, which in similar experimental settings is cleaved at positions 11, 22, and 36 (35), the shorter 50-aa-long sequence revealed a novel cleavage site at position 25.…”
Section: Discussionmentioning
confidence: 99%
“…Because the N-terminal portion of AnxA1 is a substrate for neutrophil-derived, PR-mediated cleavage and inactivation (15,16), we next assessed the cleavage of AnxA1 2-50 by HNE and PR3. This analysis demonstrated that cleavage at the C-terminal side of Val 25 was prominent and a common recognition site for both enzymes (Fig.…”
Section: Substitution Of Val 25 Yields a Cleavage-resistant Peptide Wmentioning
confidence: 99%
See 1 more Smart Citation
“…2 mg of a pcDNA3.1 plasmid with c-Myc tagged on the N terminus and FLAG tagged on the C terminus (MF-ANXA1) to over-express ANXA1 was transfected into cells. MF-ANXA1 plasmid was generated as reported previously 51 and kindly gifted by Prof. Mauro Perretti (William Harvey Research Institute, Barts and The London School of Medicine and Dentistry, Queen Mary University of London, London, UK). pcDNA3.1 empty vector was used as control.…”
Section: Matrigel Invasion Assaymentioning
confidence: 99%
“…Other aspects of host defence were also explored in the current study, namely the direct anti-microbial actions of AnxA1 and its N-terminal truncated peptides. The N-terminus of AnxA1 is reported to contain cleavage sites for elastase (Smith et al 1990) and proteinase 3 enzymes which cleave at valine and alanine residues (Vong et al, 2007). The data indicates that the majority of the imunoreactive AnxA1 protein detected in human saliva samples is in the truncated form (~33kD).…”
Section: (Insert Figure 2 Around Here) Discussionmentioning
confidence: 66%